Farm exposure and time trends in early childhood may influence DNA methylation in genes related to asthma and allergy. Issue 3 (25th January 2013) - Michel, S.; Busato, F.; Genuneit, J.; Pekkanen, J.; Dalphin, J.‐C.; Riedler, J.; Mazaleyrat, N.; Weber, J.; Karvonen, A. M.; Hirvonen, M.‐R.; Braun‐Fahrländer, C.; Lauener, R.; et al.
Abstract Background Genetic susceptibility and environmental influences are important contributors to the development of asthma and atopic diseases. Epigenetic mechanisms may facilitate gene by environment interactions in these diseases. Methods We studied the rural birth cohort PASTURE (Protection against allergy: study in rural environments) to investigate (a) whether epigenetic patterns in asthma candidate genes are influenced by farm exposure in general, (b) change over the first years of life, and (c) whether these changes may contribute to the development of asthma. DNA was extracted from cord blood and whole blood collected at the age of 4.5 years in 46 samples per time point. DNA methylation in 23 regions in ten candidate genes (ORMDL1, ORMDL2, ORMDL3, CHI3L1, RAD50, IL13, IL4, STAT6, FOXP3, and RUNX3) was assessed by pyrosequencing, and differences between strata were analyzed by nonparametric Wilcoxon–Mann–Whitney tests. Results In cord blood, regions in ORMDL1 and STAT6 were hypomethylated in DNA from farmers' as compared to nonfarmers' children, while regions in RAD50 and IL13 were hypermethylated (lowest P‐value (STAT6) = 0.001). Changes in methylation over time occurred in 15 gene regions (lowest P‐value (IL13) = 1.57*10−8). Interestingly, these differences clustered in the genes highly associated with asthma (ORMDL family) and IgE regulation (RAD50, IL13, and IL4), but not in the T‐regulatory genes (FOXP3, RUNX3). Conclusions In this first pilot study, DNA methylation patterns change significantly in early childhood in specific asthma‐ and allergy‐related genes in peripheral blood cells, and early exposure to farm environment seems to influence methylation patterns in distinct genes.